(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1916)
The symbols inscribed on the Rayne stone are the Mirror Case, the Double Crescent, and a Rectangle with rod attached, of which no previous example has been found on any of the Scottish sculptured stones. The diorite stone at Culsalmond has a small plain incised cross formed of two lines crossing each other at right angles near the centre.